2021
DOI: 10.1097/coc.0000000000000809
|View full text |Cite
|
Sign up to set email alerts
|

Intercostobrachial Nerve (ICBN) Preservation Versus Sacrifice in Axillary Dissection

Abstract: Objectives: Whether to preserve or sacrifice the intercostobrachial nerves (ICBN) is a controversial issue. In this trial, we aim to assess the effects of preservation of the ICBN during axillary dissection for patients with breast cancer in terms of pain score immediately postoperatively and several hours later, need for simple analgesia and narcotics, numbness and arm swelling.Materials and Methods: This is a single-institution, single-surgeon randomized controlled trial where a sample of 48 patients with br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The systematic review and meta-analysis include twenty-three studies published between 1999 and 2023. Six studies were conducted on cadaveric samples [ 9 , 15 , 16 , 23 , 27 , 28 ], and seventeen were performed intraoperatively [ 2 4 , 6 , 10 14 , 17 – 22 , 24 26 ]. The studies exhibit a broad geographic distribution, with 10 studies from Asia [ 3 , 4 , 9 12 , 16 , 18 , 21 , 28 ], 6 from Europe [ 6 , 14 , 19 , 20 , 25 , 26 ], 4 from South America [ 2 , 15 , 22 , 24 ], and one each from North America [ 23 ], Africa [ 17 ], and Australia [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review and meta-analysis include twenty-three studies published between 1999 and 2023. Six studies were conducted on cadaveric samples [ 9 , 15 , 16 , 23 , 27 , 28 ], and seventeen were performed intraoperatively [ 2 4 , 6 , 10 14 , 17 – 22 , 24 26 ]. The studies exhibit a broad geographic distribution, with 10 studies from Asia [ 3 , 4 , 9 12 , 16 , 18 , 21 , 28 ], 6 from Europe [ 6 , 14 , 19 , 20 , 25 , 26 ], 4 from South America [ 2 , 15 , 22 , 24 ], and one each from North America [ 23 ], Africa [ 17 ], and Australia [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reproduction of medial arm symptoms with palpatory exam to the second and third rib angle can be an indicator of this diagnosis. The history of the upper thoracic rib cage or axillary lymph node surgery can directly affect the intercostobrachial nerve via trauma or indirectly by affecting the arthrokinematics and biomechanics of the upper rib cage [20]. Entrapment of the intercostobrachial nerve affected by indirect factors can be managed by addressing soft tissue restrictions in the pectoral region and by restoring the arthrokinematics of the second and third costovertebral and costotransverse joint.…”
Section: Discussionmentioning
confidence: 99%
“…Signs and symptoms reported are burning pain, shooting pain, pressure sensation, and/or numbness (incidence and risks, 2012). The contribution of the resected intercostobrachial nerve (ICBN) with axillary lymph node dissection resulting in hypoesthesia/anesthesia together with static mechanical allodynia or persistent pain has been evaluated multiple times in surgical studies for breast cancer (Ahmed et al, 2014; Andersen et al, 2014; Melhem et al, 2021; Mustonen et al, 2019; Zhu et al, 2014). A recent systematic review by Dams et al (2021) concluded that BCS with persistent pain in the surgical area showed local disturbances in thermal detection and increased TS of pain.…”
Section: Altered Somatosensory Functioning In Breast Cancer Survivors...mentioning
confidence: 99%